Import Dependency and Trade Deficit in Nepal: An ARDL Bounds Testing Approach - Adhikari, Gyan Mani; Mishra, Avinindra Dutta; Chhetri, Santosh; Karki, Padam Bahadur (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2025)
This study examines the long-run relationship between import dependency and trade deficit in Nepal using the Autoregressive Distributed Lag (ARDL) bounds testing approach. Three distinct models with different dependent variables—import-to-GDP ratio, trade deficit, and export-import ratio—are analyzed using annual time series data from 1975 to 2023. The results confirm the existence of cointegration relationships in all three models at the 10 percent significance level. The exchange rate emerges as the most significant determinant of trade imbalances, with substantial positive effects on import dependency and the trade deficit. Remittances demonstrate a significant negative relationship with trade deficit, suggesting their potential in alleviating trade imbalances. The error correction terms indicate varying adjustment speeds across models, reflecting structural rigidities in Nepal’s economy. These findings have significant policy implications for addressing Nepal’s persistent trade deficit through effective exchange rate management, the productive utilization of remittances, and structural economic transformation.